DDOS avoidance strategy for service avalibilty - AlRashidi, Bedour Fahhad Hamed (2015)
A Distributed Denial of Service (DDoS) attack is widely regarded as a major threat for the current Internet because of its ability to create a huge volume of unwanted traffic and avoid the service for the users. It is hard to detect and respond to DDoS attacks due to the large and complex network environments. When the DDoS attack is being executed, in most of the cases, the target cannot provide its services normally. This is not a significant problem for non-critical application, but for availability critical services such as stock financial, stock market, or governmental, the effect of the attack may involve huge damage. In this thesis, the distancebased DDoS detection technique was introduced by developing prototype as a real simulation for different protocols flood in vb.net. The technique was tested by using the CAIDA DDoS Attack 2007 Dataset. The method for discreet event simulation (DES) was applied to get the result after applying DDoS attack protection. The attacks are detected by analyzing distance values and traffic rates. The distance information of a packet can be inferred from the Time to- Live (TTL) value of the IP header.